UJI KANDUNGAN PROTEIN FORMULASI KERANG/KOTENG (Pilsbryoconcha exilis) MENJADI MP-ASI DI DESA LAMASI PANTAI - Mardiana; Hamdan, Dian Furqani (Media Farmasi Indonesia, 2021)
Based on RISKESDAS data on the amount of stunting in children under five in Indonesia, this study conducted a test of the nutritional content of protein in local foodstuffs of the coastal Lamasi village community, namely Koteng mussels (Pilsbryoconcha exilis). This is to support the government of South Sulawesi to reduce the prevalence rate of stunting (very short and short) who experience malnutrition and malnutrition. This study only focuses on testing the protein content as the main substance and nutrition for the growth and development of toddlers, while the method used in this study is the shellfish formulation which is done manually where the raw material is boiled and dried then smashed into powder and then tested for protein content using the Kjeldahl method in the Sucofindo laboratory weighing 500 grams. The results of the protein content test of the formulation of Koteng shellfish (P.exilis) resulted in a protein content of 56.66%. As for the preparation of MP-ASI recipes with a collection of river clams worth 70 g, 4 g skim milk, 6 g rice flour, and 2 g vegetable oil, each containing protein worth 7,9% successively 6,5%; 9,6%; 2%